2010
DOI: 10.1111/j.1744-7348.2010.00438.x
|View full text |Cite
|
Sign up to set email alerts
|

In the light of new greenhouse technologies: 1. Plant‐mediated effects of artificial lighting on arthropods and tritrophic interactions

Abstract: This review describes the effects of the current and emerging lighting technologies on plants, and the plant‐mediated effects on herbivorous and beneficial arthropods in high‐technology year‐round greenhouse production, where light quality, quantity and photoperiod differ from the natural environment. The spectrum provided by the current lighting technology, high‐pressure sodium lamp (HPSL), differs considerably from that of solar radiation. The major plant‐mediated effects on arthropods were predicted to resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
0
16

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 150 publications
1
87
0
16
Order By: Relevance
“…There are nevertheless some promising reports that irradiation with light in the range of 500-600 nm results in an increase of ascorbic acid and anthocyanin content (29) and that yellow light with wavelengths in the range of 580-600 nm may infl uence gene expression in plants during growth (30). However, there are no literature data available about the infl uence of irradiation with yellow LED light during storage on secondary metabolites of fruits and vegetables.…”
Section: Introductionmentioning
confidence: 88%
“…There are nevertheless some promising reports that irradiation with light in the range of 500-600 nm results in an increase of ascorbic acid and anthocyanin content (29) and that yellow light with wavelengths in the range of 580-600 nm may infl uence gene expression in plants during growth (30). However, there are no literature data available about the infl uence of irradiation with yellow LED light during storage on secondary metabolites of fruits and vegetables.…”
Section: Introductionmentioning
confidence: 88%
“…It is possible to enhance photosynthetic performance modifying the spectral energy distribution (light quality) of lamps. 14 The imbalance in excitation of the photosystem I and II leads to a loss of quantum yield for CO 2 fixation. 6 In this research, common dandelion and purple coneflower showed different gas exchange dynamics under LED and FLUORA treatments, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This result is of key importance, as plant blue light photoreceptors influence phototropism, stomata opening, leaf growth and chlorophyll production, while phytochromes absorb red light wavelengths, that initiate flowering, seed germination and root development. 14,15 LEDs are used in numerous applications, including shelf-style lighting in growth rooms and in fullcycle plant production in greenhouses. 2 These lights are also used to determine the better combinations of bulbs, usually of blue and red wavebands, able to produce optimal growth for different species.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is known that predatory mites perform differently under varying light intensities and day lengths (Auger et al, 1999;Kazak et al, 2004;Weintraub et al, 2005), only a few studies have investigated possible interactions between these factors, and the impacts this may have on greenhouse BCAs (Johansen et al, 2011;Weintraub et al, 2005;Zilahi-Balogh et al, 2007). The actions of phytoseiids can be impacted directly by light reception and photophase (Gerson et al, 2003), or indirectly, through such effects as altered nutritional quality of the plant, plant defense mechanisms, volatile compound emission levels (Shipp et al, 2009;Vanninen et al, 2010) and behaviours associated with activity and movement when dehydrated (Gerson et al, 2003). Some strains of N. cucumeris enter a reproductive diapause or inactive state when they are exposed to short day lengths of less than 12-14h of light per day (Heinz et al, 2004), thus, a non-diapausing strain of N. cucumeris has been selected for use in greenhouses (Zilahi-Balogh et al, 2007).…”
Section: Humidity and Vapor Pressure Deficitmentioning
confidence: 99%